Weight Status and Satisfaction With Healthcare Received in the U.S. And Georgia - Saswat Panda; Koichiro Otani; Janani Thapa (Georgia Southern University, 2016)
Background: Two-thirds of the U.S. population is overweight or obese, and, in Georgia, adult obesity rates are among the highest. Obesity is a risk factor for diabetes, heart disease, stroke, and some types of cancer, and adherence to treatment of such disease conditions is affected by patients' perception of healthcare received. The present study examined the association between weight status and satisfaction with healthcare received in the U.S. and in Georgia. Methods: The association between weight status and satisfaction with healthcare received in the U.S. and Georgia was examined using multiple logistic regression analyses, controlling for demographic and other healthcare-related variables. The data used were from the 2013 Behavioral Risk Factor Surveillance System (BRFSS) dataset. Results:There were 265,468 complete cases for the U.S., 66% (181,911) were overweight or obese. The odds of being very satisfied with healthcare received was lower for the underweight, overweight, and obese groups by 11.8% (p Conclusions: The probability of being very satisfied with healthcare received is lower for obese and overweight patients. Improvements in healthcare services provided to these individuals are needed to ensure satisfaction and adherence to treatment of chronic diseases, including weight loss treatment and management.